Legal Maxims in Sharia Economic Law: Epistemology and Methodological Roles of Qawāʿid al-Fiqhiyyah - Mualim Mualim; Beni Ahmad Saebani; Aulia Naufal (UIN Siber Syekh Nurjati Cirebon, 2025)
Abstract The rapid development of the Islamic economic system in Indonesia has highlighted the urgency of a solid legal framework, particularly through the application of Islamic legal maxims (Qawāʿid al-Fiqhiyyah). This study aims to analyze the concept, epistemology, and implementation of legal maxims within Sharia economic law. Using a qualitative descriptive approach through library research and normative juridical analysis, the study examines primary sources such as the Qur’an, Sunnah, juristic consensus, and classical as well as contemporary scholarly works. The findings reveal that Qawāʿid al-Fiqhiyyah function as an epistemic tool that bridges normative texts and contemporary economic practices, offering methodological flexibility to address modern financial transactions. The discussion demonstrates their practical application in Islamic financial contracts, fatwa formulation by the National Sharia Council (DSN-MUI), and judicial considerations in Sharia Economic Courts. This study concludes that legal maxims are not merely theoretical constructs but a vital epistemological foundation for developing adaptive, contextual, and solution-oriented Sharia economic law in line with maqāṣid al-sharīʿah. Keywords: Islamic Economic Law; Qawāʿid al-Fiqhiyyah; Islamic Legal Epistemology; Islamic Economics; Contemporary Sharia Regulation.